2009
DOI: 10.22146/ijcn.17716
|View full text |Cite
|
Sign up to set email alerts
|

Pola asuh, pola makan, asupan zat gizi dan hubungannya dengan status gizi anak balita masyarakat Suku Nuaulu di Kecamatan Amahai Kabupaten Maluku Tengah Provinsi Maluku

Abstract: Background: Nomadic life of Nuaulu Tribe results in rearing pattern, eating pattern, and food consumption which affect their nutritional status.Objective: To identify the relationship between rearing pattern, eating pattern, nutrient intake, and nutritional status of under-fives of Nuaulu tribal community at Subdistrict of Amahai, District of Maluku Tengah, Province of Maluku.Method: This was an observational analytical study with cross sectional design. Subjects of the study were 68 under-fives of age 12 to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
2
0
6
Order By: Relevance
“…The results of this study suggested that the majority of children under five in Karanglewas Health Center got an adequate nutritional intake of 55.2%, while the remaining low nutritional intake of 44.8%. This is Advances in Health Sciences Research, volume 20 consistent with research conducted on toddlers in the Maluku region which explains that most toddlers get an adequate nutritional intake of 73.6% [20].…”
Section: This Study Illustrates the Proportion Of Giving Mpasi To Chisupporting
confidence: 78%
“…The results of this study suggested that the majority of children under five in Karanglewas Health Center got an adequate nutritional intake of 55.2%, while the remaining low nutritional intake of 44.8%. This is Advances in Health Sciences Research, volume 20 consistent with research conducted on toddlers in the Maluku region which explains that most toddlers get an adequate nutritional intake of 73.6% [20].…”
Section: This Study Illustrates the Proportion Of Giving Mpasi To Chisupporting
confidence: 78%
“…14 Anak dengan pola asuh yang kurang baik akan lebih berisiko memiliki status gizi pendek dibandingkan dengan anak dengan pola asuh yang baik. 15 Pendapatan keluarga merupakan salah satu faktor yang memiliki hubungan dengan status gizi anak.…”
Section: Pendahuluanunclassified
“…Keluarga dengan status ekonomi tinggi memiliki kemampuan lebih baik dalam memenuhi kebutuhan asupannya dibandingkan dengan keluarga dengan pendapatan rendah. 14,15 Penelitian-penelitian terkait hubungan antara karakteristik keluarga 4,13-15 dan asupan makanan [7][8][9] dengan stunting telah dilakukan di berbagai daerah, namun sejauh pengamatan kami belum ada penelitian yang menggabungkan karakteristik keluarga dan asupan makanan dalam satu penelitian di kota Semarang. Berdasarkan uraian diatas maka peneliti tertarik melakukan penelitian untuk melihat hubungan antara karakteristik keluarga berupa pengetahuan gizi ibu, pola asuh dan pendapatan keluarga serta tingkat kecukupan asupan zat gizi makro (energi, karbohidrat, lemak dan protein) dan mikro (Vitamin A, Kalsium, Seng dan Zat Besi) dengan kejadian stunting pada baduta.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations